Agricultural landscapes and ecosystem services in South-East Asia–the LEGATO-Project - Settele, Josef; Spangenberg, Joachim H.; Heong, Kong Luen; Burkhard, Benjamin; Bustamante, Jesus Victor; Cabbigat, Jimmy; Van Chien, Ho; Escalada, Monina; Grescho, Volker; Hai, Le Huu; Harpke, Alexander; Horgan, Finbarr G.; et al. (Elsevier, 2015)
The present special feature of Basic and Applied Ecology focusses on the LEGATO project: “Land-use intensity and Ecological enGineering—Assessment Tools for risks and Opportunities in irrigated rice based production systems” (http://www.legato-project.net/), which aims to advance long-term sustainable development of irrigated rice landscapes against risks arising from multiple aspects of global change. LEGATO is part of the framework programme ‘FONA—Research for Sustainability’, a funding scheme of the German Ministry of Education and Science—BMBF